Electrical field of electrical appliances versus distance: A preliminary analysis - Mustafa N.B.A.; Nordin F.H.; Ismail F.A.A.; Alkahtani A.A.; Balasubramaniam N.; Hock G.C.; Shariff Z.A.M. (Institute of Physics Publishing, 2023)
Every household electrical appliance that is plugged in emits electric field even if it is not operating. The source where the appliance is plugged into and the components of household electrical appliance contribute to electric field emission. The electric field may cause unknown disturbance to the environment or also affect the human health and the effect might depends on the strength of the electric field emitted by the appliance. This paper will investigate the strength of the electric field emitted by four different electrical appliances using spectrum analyser. The strength will be captured at three different distances; (i) 1m (ii) 2m and (iii) 3m and analysis of the strength of the electrical field is done based on the three different distances. The measurement results show that the strength of the electric field is strongest when it is captured at 1m and the weakest at 3m from the electrical appliance. The results proved that the farther an object is located from the electrical appliance; the less effect the magnetic field has. Published under licence by IOP Publishing Ltd.